Front Cover: A Phosphorus Analogue of Acenaphthylene (Eur. J. Org. Chem. 38/2017). Issue 38 (19th September 2017) - Huang, Haiyang; Wei, Zhibin; Wang, Mincan; Duan, Zheng; Mathey, François
Abstract : The Front Cover shows the thermal splitting of a 7‐phosphanorbornene ylide, giving a norbornadiene by‐product and a stable 2‐methoxy‐phosphaalkene. The example shown on the cover is the synthesis of an original 1‐phospha‐2‐methoxyacenaphthylidene, which can serve as a potentially general route to phosphaalkenes. More information can be found in theFull Paper by Z. Duan, F. Mathey et al.